2016
DOI: 10.1111/cote.12214
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the measurement of photochromic lens performance

Abstract: The principles, characteristics, and measurement methodology of photochromism of plastic ophthalmic lenses are briefly introduced and discussed. The factors influencing measurement variation and accuracy, including the preconditioning process, measurement device, and procedure, were investigated on ophthalmic photochromic lenses covering both photocasting and photocoating lens technologies. By design of experiment, factors affecting the measurements were studied using a photochromic measurement rig with refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The transmittance of the colorless state was measured first. Second, to measure the transmittance of the colored state, the lens was placed in the photochromic lens tester and was activated by 10 pulses in 12 s. After the lens had quickly been moved to the spectrophotometer, the transmittances were recorded at the intervals of 0, 120, 240, and 360 s. If absorbance (A) was needed, it was calculated by A = 2 -log(T) as an equation of the relationship between A and transmittance (T, %) [2]. In addition, after storing for at least 12 h at room temperature, the transmittance was again measured at intervals of 0, 30, 60, 90, and 120 s at the wavelength with the maximum absorbance obtained from the previous measured transmittance.…”
Section: Measurement Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmittance of the colorless state was measured first. Second, to measure the transmittance of the colored state, the lens was placed in the photochromic lens tester and was activated by 10 pulses in 12 s. After the lens had quickly been moved to the spectrophotometer, the transmittances were recorded at the intervals of 0, 120, 240, and 360 s. If absorbance (A) was needed, it was calculated by A = 2 -log(T) as an equation of the relationship between A and transmittance (T, %) [2]. In addition, after storing for at least 12 h at room temperature, the transmittance was again measured at intervals of 0, 30, 60, 90, and 120 s at the wavelength with the maximum absorbance obtained from the previous measured transmittance.…”
Section: Measurement Proceduresmentioning
confidence: 99%
“…Photochromic lenses are spectacle lenses involving a light-induced reversible change of color, i.e., they darken on exposure to ultraviolet (UV) rays in the presence of outdoor sunlight and return to their clear state in the absence of activating light under indoor conditions [1,2]. These lenses are used for reducing glare discomfort [3] and disability [4], improving photostress recovery [5], and protecting the eyes from UV radiation [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these lenses are utilize photochromic molecules which are activated by exposure to UV. Although research on the perks of these lenses is still underdeveloped, few studies have shown their efficacy in managing AMD, dry eye syndrome, and photophobia [16][17][18] . However, the only commercial contact lens with transition properties currently available is the ACUVUE® OASYS with Transitions.…”
Section: Introductionmentioning
confidence: 99%